Innovative approaches to sexual and reproductive health and rights - Stienen, Petra (2023)
Sexual and reproductive health and rights (SRHR), which are related to bodily autonomy and selfdetermination in sexuality and reproduction, are particularly relevant to gender equality but concern every individual. Access to these rights should be ensured without discrimination based on any ground. This objective should be high in the priorities of legislators and policy makers. Innovation in science and technology, in areas such as communication and online medical consultation and prescription, facilitates the implementation of this policy priority.
Keywords: ⛔ No DOI found